Distributing synthetic focusing over multiple push-detect events enhances shear wave elasticity imaging performance - Ahmed, Rifat (IEEE Trans Ultrason Ferroelectr Freq Control, 2019)
Plane wave imaging is a commonly used method for tracking waves during shear wave elasticity imaging (SWEI), but its unfocused transmission beam reduces tracking accuracy and precision. Coherent compounding minimizes this problem, but SWEI’s stringent frame rate requirement and the coarse pitch of most clinical transducers limit its effectiveness. Synthetic aperture imaging (SAI) is an alternate ultrasound imaging approach with a much tighter focus than plane wave imaging, but its lower transmission power has deterred researchers from using SAI in SWEI. Hadamard-encoded multi-element SAI can overcome this limitation. However, only a limited number of sub-apertures (3 to 5) can be transmitted in a single push-detect event. We have developed methods to distribute more sub-apertures or more compounding angles over multiple push-detect events. In this paper, we report the results of experiments conducted on phantoms to assess SWEI’s performance when using Hadamard-encoded distributed-multi-element synthetic aperture imaging (HDMSA) or distributed plane wave compounding (DPWC) to track shear waves. Tracking shear waves with HDMSA improved the elastographic signal-to-noise ratio (SNR(e)) by 61.6% to 89.5% depending on the phantom employed. Similarly, DPWC tracking improved SNR(e) by 56.2% to 93.3% for the same group of phantoms. Compared to focused ultrasound tracking (at the focus), SNR(e) improved by 28.6% and 32.5% when tracking shear waves with HDMSA and DPWC, respectively. Long acquisitions could introduce decoding errors that decrease performance when performing HDMSA tracking within the clinical setting. Nevertheless, the results of studies performed on the bicep muscle of three healthy volunteers demonstrate that for stationary organs tracking shear waves with HDMSA yielded repeatable elastograms that offer better elastographic performance than those produced with current tracking methods.